Pantang : perspectives and realities of mortality - Ngian, Xuan Rong (2017)
‘Pantang’ attempts to discuss the significance of death and remembrance of identity through a multidimensional exhibition. Using the play of perspectives and simulation of different realities of mortality, ‘Pantang’ intends to open a discourse around cultural practices, remembrance and respect on our individuality; for who you are is intrinsically tied to your own life and death. These realities will reflect how death is confronted in the contemporary society. Through the exhibition, “pantang-ness” is being deconstructed and viewers will be led to confront to their identity as they explore the different dimensions of life and death.